PERANCANGAN SISTEM KUESIONER DENGAN MENGGUNAKAN SYSTEM USABILITY SCALE UNTUK ANALISIS EFEKTIFITAS E-OFFICE TERHADAP PENGGUNA JEJAK SURAT PADA APLIKASI NASKAH DINAS ELEKTRONIK PEMERINTAH PROVINSI DKI JAKARTA - Suci Ayu Peritami; Galuh Saputri (CV. Multi Kreasi Media, 2023)
The design of this questionnaire system utilizes the System Usability Scale (SUS) with the aim of analyzing the effectiveness of the e-office on users' tracking of documents within the Electronic Official Correspondence Application of the Jakarta Provincial Government. The analysis of data obtained from the SUS questionnaire will provide valuable information regarding potential improvements required in the application to enhance its effectiveness.This qualitative method was conducted through the administration of a System Usability Scale (SUS) questionnaire to the active users of the aplikasi naskah dinas elektronik in the Provincial Government of Jakarta. The SUS questionnaire consists of ten questions with a five-point Likert scale, in which the respondents provide a rating based on the level of agreement ranging from